Estimates of personal savings functions for West Malaysia based on 1957-58 household budget survey data - Shahrum Hashim,; Abdul Halim Ismail, (Universiti Kebangsaan Malaysia, 1974)
This paper estimates personal savings functions for West Malaysia from the data collected in the 1957-58 Household Budget Survey by the Department of Statistics. Only the simple Keynesian functions are estimated. These are fitted to the data for all sample households as well as for these households stratified into the urban and the rural sectors and the Malay, Chinese and Indian ethnic groups.